2023
DOI: 10.3389/fsurg.2023.1132277
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of subcutaneous injection of different concentrations of methylene blue after hemorrhoidectomy: A retrospective study

Abstract: ObjectiveSubcutaneous injection of methylene blue around the anus may help reduce postoperative pain. However, the concentration of methylene blue is still controversial. Therefore, Our study aims to investigate the efficacy and safety of different methylene blue injected concentrations subcutaneously in pain treatment after hemorrhoidectomy.MethodsA total of 180 consecutive patients with grade III or IV hemorrhoids from March 2020 to December 2021 were reviewed. All patients underwent hemorrhoidectomy under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Within this range of 87 drugs, a diverse landscape emerged: ketamine (NCT04248205) was under active clinical investigation for hemorrhoids, fulvestrant was supported by preclinical in vitro models demonstrating potential efficacy for hemorrhoids ( Fanyu Meng et al, 2022 ), and methylene blue was supported by case series evidence for hemorrhoids ( Baldiwala and Trivedi, 2022 , Long et al, 2023 ), as shown in Fig. 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this range of 87 drugs, a diverse landscape emerged: ketamine (NCT04248205) was under active clinical investigation for hemorrhoids, fulvestrant was supported by preclinical in vitro models demonstrating potential efficacy for hemorrhoids ( Fanyu Meng et al, 2022 ), and methylene blue was supported by case series evidence for hemorrhoids ( Baldiwala and Trivedi, 2022 , Long et al, 2023 ), as shown in Fig. 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Fulvestrant, an estrogen receptor antagonist, has shown promise in preclinical in vitro models by inhibiting ERα, thereby reducing VEGF expression and mitigating postoperative hemorrhoid edema ( Fanyu Meng et al, 2022 ). Methylene blue, supported by case series evidence, demonstrates anti-inflammatory effects by suppressing nitric oxide production, ultimately alleviating post-hemorrhoidectomy pain ( Baldiwala and Trivedi, 2022 , Long et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there were no significant differences in complications between the two concentrations. This study concludes that perianal subcutaneous injection of 0.1% methylene blue is not only as effective as 0.2% in treating posthemorrhoidectomy pain but also safer (39). Accordingly, our study aimed to investigate the impact of an intradermal injection of methylene blue on postoperative pain management following hemorrhoidectomy compared to a control group receiving Marcaine.…”
Section: Discussionmentioning
confidence: 98%